Correction: Measurement of number concentrations and sizes of Au nano-particles spiked into soil by laser ablation single particle ICPMS. Issue 11 (22nd October 2020) - Tuoriniemi, Jani; Holbrook, Timothy R.; Cornelis, Geert; Schmitt, Melanie; Stärk, Hans-Joachim; Kooijman, Ellen; Wagner, Stephan
Abstract : Correction for 'Measurement of number concentrations and sizes of Au nano-particles spiked into soil by laser ablation single particle ICPMS' by Jani Tuoriniemi et al., J. Anal. At. Spectrom., 2020, 35, 1678–1686, DOI: ; 10.1039/D0JA00243G